The Study of Indoor Air Quality and Ventilation Rate at Pagoh Residental College - Mohd Sallehudin, Abdul Lathif (Progress in Engineering Application and Technology, 2023)
Indoor air quality (IAQ) issues are not new in Malaysia. (IAQ) continues to be an important issue affecting occupants’ health, comfort, satisfaction, and productivity. The main research objectives Compare (IAQ) parameters and ventilation rate with standards. The parameter of IAQ will be measure and recorded the data and the location chosen was in UTHM Pagoh Residental College where a selected room was in the students’ house. There is an experiment by decay method will be conducted to determine the ventilation rate. the parameter of IAQ will be measure and recorded the data. Part 2 is an experiment of by decay method will be conducted to determine the ventilation rate. A Multi-Function Environmental Meter and Multi-Function Handled Indoor Air Quality Monitor will be used to measure the IAQ parameters. The comparison of standard is made based on appropriate standard used in Malaysia for IAQ and Air Change Rate. Hence, the result shows that not all parameter comply with the IAQ while the Air Change Rate was good in fully utilized of openings. In summary, for better ventilation the occupants may open the window at least three times every day to ’dilute’ the contaminated air and make sure the furniture layout promotes ventilation.